Fault detection in waste water treatment plant using statistical analysis & machine learning - Haque, Md. Ezazul; Islam, Md. Mazed Ul; Rahat, Noor A Elahi; Amin, Md. Mahmudul (Brac University, 2019)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2019.